Modified ASO conjugates encapsulated with cytidinyl/cationic lipids exhibit more potent and longer-lasting anti-HCC effects - Yufei Pan; Jing Guan; Yujing Gao; Yuejie Zhu; Huantong Li; Hua Guo; Qianyi He; Zhu Guan; Zhenjun Yang (Elsevier, 2023)
Antisense oligonucleotides (ASOs) are a class of therapeutics targeting mRNAs or genes that have attracted much attention. However, effective delivery and optimal accumulation in target tissues in vivo are still challenging issues. CT102 is an ASO that targets IGF1R mRNA and induces cell apoptosis. Herein, a detailed exploration of the tissue distribution of ASOs delivered by liposomes was carried out. A formulation that resulted in increased hepatic accumulation was identified based on multiple intermolecular interactions between DCP (cytidinyl/cationic lipid DNCA/CLD and DSPE-PEG) and oligonucleotides, including hydrogen bonding, π-π stacking, and electrostatic interactions. The structurally optimized CT102s present a novel strategy for the treatment of hepatocellular carcinoma. The gapmer CT102MOE5 and conjugate Glu-CT102MOE5 showed superior antiproliferation and IGF1R mRNA suppression effects at 100 nM in vitro and achieved greater efficacy at a lower dose and administration frequency in vivo. Combined transcriptome and proteome analyses revealed that additional associated targets and functional regulations might simultaneously exist in ASO therapy. These results showed that a combination of lipid encapsulation and structural optimization in the delivery of oligonucleotide drugs has favorable prospects for clinical application.